THE EFFECT OF PUBLIC HOUSING CONSTRUCTION ON ECONOMIC GROWTH IN INDONESIA - Cahyo, Heru; Purnomo, Sodik Dwi; Retnowati, Diah; Zumaeroh, Zumaeroh; Badriah, Lilis Siti; Sambodo, Herman (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2022)
The development of public housing infrastructure can encourage the opening of isolated areas, reduce production costs, create new centers of economic activity, expand employment opportunities, increase consumer purchasing power, and trigger economic growth at regional and national levels. This study investigates the effect of public housing on economic growth in Indonesia. The control variables included telecommunications, electricity, and education. The research method used was multiple linear regression with a panel data approach in 34 provinces of Indonesia from 2011 to 2019. The results show that telecommunications and education have a positive and significant impact on economic growth in Indonesia. Meanwhile, housing and electricity have no significant effect on economic growth in Indonesia. These results imply a need to evaluate the benefits of public housing development. Telecommunication infrastructure development must be evenly distributed so people can access the internet to support economic activities. In addition, the government must formulate effective policies so that the people of Indonesia can access education equally.JEL: H41, H44, H53, H54ABSTRAKInfrastruktur perumahan yang layak akan meningkatkan kualitas hidup masyarakat, sehingga meningkatkan produktivitas serta akan mendorong pertumbuhan ekonomi daerah dan nasional. Studi ini mengindentifikasi pengaruh perumahan rakyat terhadap pertumbuhan ekonomi di Indonesia. Penelitian ini menggunakan variabel kontrol telekomunikasi, listrik, dan pendidikan. Metode penelitian yang digunakan adalah regresi linier berganda dengan pendekatan data panel pada 34 provinsi di Indonesia periode 2011-2019. Hasil penelitian menunjukkan bahwa telekomunikasi dan pendidikan berpengaruh positif dan signifikan terhadap pertumbuhan ekonomi di Indonesia. Sementara itu, perumahan rakyat dan listrik tidak mempengaruhi pertumbuhan ekonomi di Indonesia. Implikasi dari hasil tersebut adalah perlunya evaluasi penerima pembangunan perumahan rakyat, serta pembangunan infrastruktur telekomunikasi harus merata agar masyarakat dapat mengakses internet untuk mendukung kegiatan ekonominya. Selain itu, pemerintah harus melakukan upaya untuk membuat pendidikan dapat diakses oleh semua orang.Kata Kunci : Pertumbuhan Ekonomi, Infrastruktur Publik, Pendidikan